Evaluation of Clinical and Demographic Characteristics of Patients Hospitalized in the Pediatric Intensive Care Unit due to Convulsive Status Epilepticus - Ülkem Koçoğlu Barlas; Nihal Akçay; Mey Talip Petmezci; Hasan Serdar Kıhtır; Osman Yeşilbaş; Kübra Boydağ Güvenç; Güner Özçelik; Esra Şevketoğlu (Galenos Yayinevi, 2021)
Introduction:Status epilepticus is an important part of pediatric intensive care hospitalizations. In this study, it was aimed to investigate the general characteristics and to share the clinical and demographical features of patients who were hospitalized due to convulsive status epilepticus.Methods:One hundred-thirty one cases were included in this study. Identity information of patients, presence of acute and chronic diseases, duration of intensive care stay and hospitalization, first seizure type, where they were admitted, number of seizures during intensive care follow-up, antiepileptics used in treatment and other treatments and the status of discharge-mortality were recorded.Results:62.6% of cases were male and the mean age of all cases was 53.69±47.14 months. The most common chronic disease was epilepsy and the most common acute disease was lower respiratory tract infection. The first admission of 34.4% of the cases was due to status epilepticus, and the rate of cases accepted from other hospitals was 60.3%. During intensive care follow-up, no convulsions were observed in 77.1% of the cases. In the first treatment, benzodiazepine infusion was used in 77.1% of the cases. The median length of stay in intensive care unit was 4 days (minimum-maximum= 3-8 days) in the benzodiazepine infusion group, and 3 days (minimum-maximum=2-3 days) in the group that was not given benzodiazepine. The other most preferred antiepileptics were levetiracetam and phenytoin in 62.6% and 39.7% of the cases, respectively. The mortality rate was found as 2.3%.Conclusion:In our study, it was observed that the majority of the patients who were hospitalized in our pediatric intensive care unit due to convulsive status epilepticus were male, convulsive status epilepticus was more common in children with chronic neurological disease, benzodiazepine infusion was the first choice for treatment and Levetiracetam was the second most commonly used antiepileptic.